Temperature and fruit selection favor seed germinations of the tropical tree Myroxylon balsamum (Fabaceae) (UNED Research Journal, 2022)
Introduction: Myroxylon balsamum is a tree species native to the Neotropics; and its populations may be declining due to logging and habitat loss. Objective: To evaluate the germinative response of seeds under three temperature conditions, and in fruits selected by seed-chamber thickness. Methods: The fruits were collected in the Central Valley of Costa Rica between November 2019 and June 2020. The germinative response was evaluated at 20ºC, 20/30ºC and 30ºC. The thickness of the seed-chambers was measured and dissected. The fruits were classified as filled (thickness ≥ 0,7cm) and as vain (thickness < 0,7cm). Seed germination within fruits was evaluated at 20ºC, 20/30ºC and 30ºC. Results: As the temperature increased, the time for 50% of the seeds to germinate decreased, and the number of seeds germinated per day, increased. However, there was contamination by pathogens, which caused seed death. Filled fruits germinated well at the three temperatures (92% at 20/30ºC; 86% at 30ºC), while in the vain fruits there was germination only at 20/30ºC (4%) and pathogen contamination could be controlled. Conclusion: The germination for this tree is favored at 20/30ºC and at 30ºC, as long as seeds remain inside fruits with subglobose seed-chambers (thickness ≥ 07cm).
Keywords: balsam tree; Costa Rica; legume; samaras; seed-chamber